2018
DOI: 10.2298/gensr1802687b
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit for est microsatellites in a tetraploid model from de novo transcriptome sequencing

Abstract: methodology provides abundant de novo assembled short contigs and holds great promise to mine numerous additional EST-SSR-containing markers for possible use in genetics population studies of tetraploid taxa within the genus Centaurium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The specificity of the microsatellite markers enabled us to analyze plant material collected directly from nature, without amplifying foreign (e.g., fungal or insect) DNA, which may give false variations when non-specific markers are used. In the previous study [36], we confirmed the transferability of the eight genic microsatellite markers, initially developed for C. erythraea , to seven other taxa, and, among them, the two studied here. Still, since EST-SSR markers are basically developed from C. erythraea transcriptome, it is not surprising that they showed higher variability in this species (Table 1) in comparison to the other two studied taxa [40,41].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The specificity of the microsatellite markers enabled us to analyze plant material collected directly from nature, without amplifying foreign (e.g., fungal or insect) DNA, which may give false variations when non-specific markers are used. In the previous study [36], we confirmed the transferability of the eight genic microsatellite markers, initially developed for C. erythraea , to seven other taxa, and, among them, the two studied here. Still, since EST-SSR markers are basically developed from C. erythraea transcriptome, it is not surprising that they showed higher variability in this species (Table 1) in comparison to the other two studied taxa [40,41].…”
Section: Discussionsupporting
confidence: 84%
“…To estimate genetic variation in natural populations of both parental species and the interspecific hybrid, the EST-SSR multilocus genotyping was performed and reported for the first time for the populations within the genus Centaurium . For this purpose, we employed newly designed genic microsatellite markers [36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations